Opportunities to improve nitrogen use efficiency in an intensive vegetable system without compromising yield. Issue 3 (12th May 2021) - Suter, Helen; Pandey, Arjun; Lam, Shu Kee; Davies, Rohan; Hassan, Rifaath; Riches, David; Chen, Deli
Abstract: Intensive vegetable cropping systems rely heavily on nitrogen (N) inputs from multiple synthetic and organic fertilizer applications. The majority of applied N is lost to the environment through numerous pathways, including as nitrous oxide (N2 O). A field trial was conducted to examine the opportunities to reduce N input in an intensive vegetable system without compromising yield. Treatments applied were control (no N), manure (M, 408 kg N ha –1 from chicken manure), grower practice (GP, 408 kg N ha –1 from chicken manure + 195 kg N ha –1 from fertilizer), and 2/3 GP (two‐thirds of the total N input in GP), all with and without 3, 4‐dimethylpyrazole phosphate (DMPP). Nitrogen recovery in the GP treatment was determined using 15 N‐labeled fertilizer. Using only manure significantly lowered celery ( Apium graveolens L.) yield and apparent N use efficiency (ANUE) compared with GP. Reducing N input by one‐third did not affect yield or ANUE. Use of DMPP increased ANUE despite no yield improvement. More than 50% of the applied N in the GP treatment was lost to the environment, with almost 10 kg N ha –1 emitted as N2 O over the season, which was 67 times more than from the control. Reducing the N input by one‐third or using manure only reduced N2 O emissions by more than 70% relative to GP. This study shows that there is a clear opportunity to reduce N input and N2 O emissions in high‐fertilizer‐input vegetable systems without compromising vegetable yield. Core Ideas: Half of the applied nitrogen (N) in intensive vegetable systems is unaccounted for. 15 N‐labeled fertilizer recovery reveals inefficiency of N applied during early crop stages. DMPP was ineffective in improving N recovery due to excessive N input. Nitrogen inputs can be reduced to reduce N2 O emissions without yield penalty.